Double-pore catalyst, preparation method thereof and application of double-pore catalyst in reaction for preparing low-carbon olefin from waste plastics

By using a dual-pore catalyst composed of ZSM-11 molecular sieve, SBA-3 all-silicon mesoporous molecular sieve and metal oxide, one-step catalytic conversion is achieved in waste plastics to generate high-quality low-carbon olefins, solving the low-carbon problem in the existing technology. It has less olefin content and has good economic and environmental benefits.

CN119327507AActive Publication Date: 2025-01-21CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202310871764.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-17
Publication Date
2025-01-21
Estimated Expiration
2043-07-17

AI Technical Summary

Technical Problem

In the prior art, the content of low-carbon olefins recovered in the chemical recycling and utilization of waste plastics is relatively small, making it difficult to effectively produce pure and high-quality low-carbon olefins.

Method used

Provide a dual-pore catalyst, including ZSM-11 molecular sieve, SBA-3 all-silica mesoporous molecular sieve and optional metal oxide. Through its preparation method and application in waste plastics, it can achieve one-step catalytic conversion and utilization of waste plastics and generate low Carbon olefins.

Benefits of technology

The dual-hole catalyst has a stable structure and high temperature resistance, can effectively improve the selectivity and yield of low-carbon olefins from waste plastics, solves the problems of recycling waste plastics and producing low-carbon olefins, and has good economic benefits and environmental protection performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119327507A_ABST
    Figure CN119327507A_ABST
Patent Text Reader

Abstract

The invention relates to the field of catalysts and the field of high polymer material recycling, and discloses a dual-pore catalyst, a preparation method thereof and application of the dual-pore catalyst in a reaction for preparing low-carbon olefin from waste plastics. The dual-pore catalyst comprises a ZSM-11 molecular sieve, an SBA-3 all-silicon mesoporous molecular sieve and an optional metal oxide, and on the basis of the total weight of the dual-pore catalyst, the content of the ZSM-11 molecular sieve is 54-90 wt%, the content of the SBA-3 all-silicon mesoporous molecular sieve is 10-40 wt%, and the content of the metal oxide is 0-6 wt%; the specific surface area of the dual-pore catalyst is 420-630 m < 2 > / g, and the pore volume is 0.3-0.5 mL / g. The double-hole catalyst is applied to the waste plastic, a new way is provided for one-step catalytic conversion and utilization of the waste plastic, the problem of waste plastic recovery is solved, and the yield of important chemical raw material low-carbon olefin is increased.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of catalysts and polymer material recycling, and in particular to a double-porous catalyst and a preparation method thereof, and application thereof in the reaction of preparing low-carbon olefins from waste plastics. Background Art

[0002] Since the advent of plastic products in the 20th century, they have been widely used in various fields around the world with the characteristics of light weight, high strength, corrosion resistance, good chemical stability, easy processing, and beautiful and practical. However, plastics are difficult to degrade naturally. Although conventional landfill technology requires little investment and is simple to operate, it will occupy a large amount of land and cause land pollution. Although incineration technology can achieve the reduction requirements and recover some energy at the same time, this process is prone to release a large amount of hydrocarbons, nitrides, sulfides and highly toxic substances, which directly threaten human and ecological health. Therefore, the recycling and high-value utilization of waste plastics as a measure to save energy and protect the environment has been widely valued by countries around the world. The methods for recycling and utilizing waste plastics mainly include classified recycling, preparation of monomer raw materials, production of clean fuel and use for power generation.

[0003] my country's plastics industry is one of the pillar industries of the national economy. At present, my country has entered the ranks of the world's major plastics countries. Under the policy background of the new plastic restriction order, the sharp decline in imports, and garbage classification, my country's waste plastic recycling companies are gradually getting rid of the old path of extensive expansion in the past, and gradually examining the industrial layout with the perspective of green development. Continue to deepen cooperation with environmental protection and sanitation companies to gradually achieve the goal of green, low-carbon and circular development. Large-scale waste plastic recycling companies with standardized operations will gradually further refine the recycled waste plastics, continue to develop and apply new technologies and new products for waste plastics, gradually expand the application field of waste plastics, and increase the added value of recycled plastic products. In the existing technology, the chemical recycling scheme for waste plastics is mainly waste plastic cracking technology. There are three basic methods for waste plastic cracking, namely: thermal cracking (one-stage method), catalytic cracking (one-stage method) and thermal cracking-catalytic modification (two-stage method). The earliest developed waste plastic cracking technology is thermal cracking technology. This technology refers to a thermal conversion process in which a thermochemical decomposition reaction occurs under high temperature and anaerobic conditions to convert large molecular weight organic matter in waste plastic products into small molecular weight liquids, fuel gas, coke and other substances. The reaction temperature of this process is generally controlled at 350-900°C. If a catalyst is added during the thermal cracking process, it is a catalytic thermal cracking technology, which can not only reduce the cracking temperature, but also improve product performance. The thermal cracking-catalytic reforming method is an improvement on the catalytic cracking method. After the waste plastics are thermally cracked, a catalyst is used to catalytically reform the cracking gas. This method has higher product quality, more flexible operation and lower operating costs than the thermal cracking method and the catalytic cracking method, but the process is more complicated.

[0004] Cracking technology has wide flexibility in treating waste plastics and good energy recovery, and is one of the waste plastic treatment technologies with broad application prospects. In the prior art, the products produced by the one-step thermal cracking method and the one-step catalytic cracking method are mainly fuel oil, and only a small amount of low-carbon olefins (ethylene, propylene, butene) can be obtained. If a large amount of low-carbon olefins are required, a two-stage method of thermal cracking-catalytic modification is required. Therefore, exploring a new chemical recovery process to produce pure and high-quality final products is an important research direction for plastic waste treatment. Summary of the invention

[0005] The purpose of the present invention is to provide a double-porous catalyst and a preparation method thereof as well as an application in the reaction of preparing light-carbon olefins from waste plastics in view of the current problem that the content of light-carbon olefins recovered in the current chemical recycling of waste plastics is low. The double-porous catalyst is applied to waste plastics to provide a new approach for the one-step catalytic conversion and utilization of waste plastics, thereby solving the problem of recycling waste plastics and increasing the production of light-carbon olefins, which are important chemical raw materials.

[0006] In order to achieve the above-mentioned object, the first aspect of the present invention provides a dual-porous catalyst, wherein the dual-porous catalyst comprises a ZSM-11 molecular sieve, an SBA-3 all-silicon mesoporous molecular sieve and an optional metal oxide, and based on the total weight of the dual-porous catalyst, the content of the ZSM-11 molecular sieve is 54-90% by weight, the content of the SBA-3 all-silicon mesoporous molecular sieve is 10-40% by weight, and the content of the metal oxide is 0-6% by weight;

[0007] The specific surface area of ​​the dual-pore catalyst is 420-630 m 2 / g, and the pore volume is 0.3-0.5mL / g.

[0008] The second aspect of the present invention provides a method for preparing the aforementioned dual-porous catalyst, wherein the preparation method comprises:

[0009] (1) mixing and contacting a ZSM-11 molecular sieve and an optional aqueous solution of a metal oxide precursor to react; then removing water and drying to obtain a microporous molecular sieve dry powder;

[0010] (2) The microporous molecular sieve dry powder and the SBA-3 all-silica mesoporous molecular sieve raw powder are mixed and ball-milled, and then calcined to obtain a dual-porous catalyst.

[0011] The third aspect of the present invention provides an application of the aforementioned dual-porous catalyst in the direct catalytic cracking of waste plastics to produce light olefins.

[0012] Through the above technical solution, compared with the prior art, the technical solution of the present invention has the following advantages:

[0013] (1) The dual-porous catalyst provided by the present invention has a stable structure and good high temperature resistance, and can ensure stability under long-term high temperature conditions in the catalytic cracking reaction of waste plastics.

[0014] (2) The dual-porous catalyst provided by the present invention includes a zeolite molecular sieve with a certain surface acidity, a mesoporous material with a larger pore size, and a metal oxide for adjusting the surface acidity and electron distribution. The chemical structure of the catalyst is conducive to the cracking of waste plastic polymers and the generation of target products, and the pore structure of the catalyst is conducive to the diffusion of raw material and product molecules during the reaction process.

[0015] (3) The bi-porous catalyst provided by the present invention can convert waste plastics into light olefins in one step when used for direct catalytic cracking of waste plastics to produce light olefins, which is a new method for chemical recycling of waste plastics. It not only solves the problem of recycling waste plastics, but also increases the production of light olefins, an important chemical raw material, and has good economic benefits.

[0016] (4) When the dual-porous catalyst provided by the present invention is used for the direct catalytic cracking of waste plastics to produce light olefins, the process conditions are mild, the operation is easy, and the requirements for the reaction device are not high.

[0017] Other features and advantages of the present invention will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] The accompanying drawings are used to provide a further understanding of the present invention and constitute a part of the specification. Together with the following specific embodiments, they are used to explain the present invention but do not constitute a limitation of the present invention. In the accompanying drawings:

[0019] Figure 1 is a small-angle X-ray diffraction (XRD) spectrum of the bi-porous catalyst A prepared in Example 1 of the present invention;

[0020] Figure 2 is a wide-angle X-ray diffraction (XRD) spectrum of the bi-porous catalyst A prepared in Example 1 of the present invention;

[0021] Figure 3 This is the pore size distribution diagram of the dual-porous catalyst A prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0022] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0023] As mentioned above, the first aspect of the present invention provides a dual-porous catalyst, wherein the dual-porous catalyst comprises a ZSM-11 molecular sieve, an SBA-3 all-silicon mesoporous molecular sieve and an optional metal oxide, and based on the total weight of the dual-porous catalyst, the content of the ZSM-11 molecular sieve is 54-90% by weight, the content of the SBA-3 all-silicon mesoporous molecular sieve is 10-40% by weight, and the content of the metal oxide is 0-6% by weight;

[0024] The specific surface area of ​​the dual-pore catalyst is 420-630 m 2 / g, and the pore volume is 0.3-0.5mL / g.

[0025] The inventors of the present invention have found that in the prior art, there is no process for directly catalytically cracking waste plastics to produce low-carbon olefins (including ethylene, propylene, and butene). The purpose of the present invention is to solve this problem. According to the inventor's understanding of the physicochemical properties of heterogeneous catalysts, the catalyst used for catalytic cracking of waste plastics to directly prepare low-carbon olefins should have a certain acidity and good hydrothermal stability. Based on the above requirements, Pentasil-type zeolite molecular sieves with a stable skeleton structure and a certain acidity are very suitable as the main component of the waste plastic cracking catalyst. As Pentasil-type zeolite molecular sieves, ZSM-11 molecular sieves and ZSM-5 molecular sieves have similar chemical compositions, and both have elliptical ten-membered ring cross-pore structures. However, compared with ZSM-5 molecular sieves, ZSM-11 molecular sieves have a more regular pore structure, better skeleton symmetry, and are more suitable for high-temperature reactions. However, similar to ZSM-5 molecular sieves, ZSM-11 zeolite molecular sieves have smaller pore sizes (pore size between 0.50-0.55nm) and smaller pore volumes (0.1-0.3cm 3 / g), while waste plastics are high-molecular products with large molecular weights and long molecular chains. During the cracking reaction of waste plastic products, it is difficult for larger reactant molecules and product molecules to diffuse between narrow channels, which not only affects the contact between reactants and active centers, but also easily leads to side reactions such as deep dehydrogenation, which in turn leads to a decrease in catalyst performance. Compared with zeolite molecular sieves, SBA-3 all-silica mesoporous molecular sieve materials have larger pore sizes (greater than 2.0nm) and larger pore volumes (up to 0.9cm 3 / g or so), which is very suitable for catalytic reactions involving macromolecules. However, SBA-3 all-silicon mesoporous molecular sieve material is an all-silicon material with extremely weak surface acidity, and is not suitable for being used alone as a catalyst to catalyze the cracking reaction of waste plastics. The inventors of the present invention found in the development and research of waste plastic cracking catalysts that if the structural advantages of all-silicon mesoporous inorganic materials and the surface acidic centers of zeolite molecular sieves are comprehensively utilized, a certain amount of SBA-3 all-silicon mesoporous molecular sieves is mixed with ZSM-11 zeolite molecular sieves, the specific surface area and pore volume of the catalyst can be effectively increased, and the internal diffusion performance in the reaction can be significantly improved.

[0026] In addition, the use of metal oxides to properly adjust the surface acidity and electron distribution of the cracking catalyst can effectively promote the cracking reaction and the generation of the target product. The dual-porous catalyst containing ZSM-11 zeolite molecular sieve, SBA-3 all-silicon mesoporous molecular sieve and metal oxides, when used as a cracking catalyst in the catalytic conversion reaction of waste plastics, can not only effectively improve the activity of the cracking catalyst, but also increase the selectivity of light olefins.

[0027] According to the present invention, preferably, based on the total weight of the dual-pore catalyst, the content of the ZSM-11 molecular sieve is 60-84% by weight, the content of the SBA-3 all-silicon mesoporous molecular sieve is 15-35% by weight, and the content of the metal oxide is 1-5% by weight; more preferably, based on the total weight of the dual-pore catalyst, the content of the ZSM-11 molecular sieve is 66-78% by weight, the content of the SBA-3 all-silicon mesoporous molecular sieve is 20-30% by weight, and the content of the metal oxide is 2-4% by weight. In the present invention, the use of the aforementioned specific content of each component can make the prepared dual-pore catalyst have better catalytic activity and higher selectivity for light olefins when used for direct catalytic cracking of waste plastics to prepare light olefins.

[0028] According to the present invention, preferably, the specific surface area of ​​the dual-pore catalyst is 500-590m 2 / g, and the pore volume is 0.34-0.46mL / g; more preferably, the specific surface area of ​​the dual-pore catalyst is 535-570m 2 / g, and the pore volume is 0.38-0.43mL / g. In the present invention, the use of the bi-porous catalyst within the above-mentioned specific parameter range can make the bi-porous catalyst have better catalytic activity and higher selectivity for light olefins when used in the direct catalytic cracking of waste plastics to prepare light olefins.

[0029] According to the present invention, the pore size of the dual-pore catalyst is bimodal, the micropore size is 0.4-0.6 nm, and the mesopore size is 2-4 nm.

[0030] According to the present invention, the SiO2 / Al2O3 molar ratio of the ZSM-11 molecular sieve is 30-300. In the present invention, the ZSM-11 molecular sieve can be obtained by commercial means. Specifically, the ZSM-11 molecular sieve can be: a ZSM-11 molecular sieve with a SiO2 / Al2O3 molar ratio of 35 purchased from Nanjing Jicang Nano Technology Co., Ltd.; a ZSM-11 molecular sieve with a SiO2 / Al2O3 molar ratio of 90 purchased from Zhuoran Environmental Protection Technology (Dalian) Co., Ltd.; a ZSM-11 molecular sieve with a model of JL-A03 (SiO2 / Al2O3 molar ratio of 50), JL-A04 (SiO2 / Al2O3 molar ratio of 80) and JL-A05 (SiO2 / Al2O3 molar ratio of 280) purchased from Zibo Jiulong Chemical Technology Co., Ltd.

[0031] According to the present invention, the metal oxide is an alkaline earth metal oxide and / or a transition metal oxide; preferably, the metal oxide is selected from one or more of magnesium oxide, calcium oxide, strontium oxide, barium oxide and zinc oxide. In the present invention, the specific metal oxide selected from the present invention can improve the surface acidity and surface electron distribution of the cracking catalyst, making the surface characteristics of the catalyst more suitable for the waste plastic cracking reaction.

[0032] According to the present invention, the preparation method of the SBA-3 all-silicon mesoporous molecular sieve raw powder includes: mixing and contacting a template, a silicon source, an inorganic acid, a metal salt and water to obtain a mixture, and crystallizing, filtering, washing and drying the mixture to obtain the SBA-3 all-silicon mesoporous molecular sieve raw powder.

[0033] According to the present invention, the template agent is a cationic surfactant, preferably one or more of dodecyltrimethylammonium bromide, tetradecyltrimethylammonium bromide, hexadecyltrimethylammonium bromide and octadecyltrimethylammonium bromide.

[0034] According to the present invention, the silicon source is an organic silicon source and / or an inorganic silicon source, preferably tetraethyl orthosilicate and / or water glass.

[0035] According to the present invention, the inorganic acid is selected from one or more of hydrochloric acid, sulfuric acid, nitric acid, phosphoric acid, acetic acid and citric acid, preferably phosphoric acid and / or acetic acid.

[0036] According to the present invention, the metal salt is selected from one or more of alkali metal chlorides, bromides, nitrates and sulfates, preferably one or more of sodium nitrate, sodium chloride, sodium bromide, sodium sulfate, potassium nitrate, potassium chloride, potassium bromide and potassium sulfate.

[0037] According to the present invention, the molar ratio of the silicon source, template, inorganic acid, metal salt and water is 1: (0.05-2.0): (0.5-10): (0.2-5.0): (20-400); preferably 1: (0.1-1.2): (1-6): (0.5-2.0): (50-200).

[0038] According to the present invention, the mixing contact conditions include: temperature of 15-50°C, preferably 20-40°C; time of 20-120 min, preferably 30-60 min. In order to facilitate uniform mixing of the various substances, according to a preferred embodiment of the present invention, the hydrolysis process is carried out under stirring conditions.

[0039] According to the present invention, the crystallization conditions include: temperature of 15-50°C and time of 3-120h; under preferred conditions, the crystallization conditions include: temperature of 20-40°C and time of 8-50h.

[0040] According to the present invention, there are no special requirements for the filtering method, and it can be a filtering method known in the art, including gravity filtration, pressure filtration, vacuum filtration or centrifugal filtration. Preferably, the filtering process specifically includes: using a suction bottle, vacuuming the bottom side of the funnel or filtering using a centrifugal filter.

[0041] According to the present invention, the washing conditions are not particularly limited. For example, the washing process may include: obtaining a solid product after filtration, repeatedly washing the solid product with distilled water (the number of washing times may be 2-10) and then filtering.

[0042] According to the present invention, the drying process can be carried out in a drying oven, and the drying conditions may include: a temperature of 60-150°C and a time of 2-30h; under preferred conditions, the drying conditions include: a temperature of 70-110°C and a time of 6-20h.

[0043] The second aspect of the present invention provides a method for preparing the aforementioned dual-porous catalyst, wherein the preparation method comprises:

[0044] (1) mixing and contacting a ZSM-11 molecular sieve and an optional aqueous solution of a metal oxide precursor to react; then removing water and drying to obtain a microporous molecular sieve dry powder;

[0045] (2) The microporous molecular sieve dry powder and the SBA-3 all-silica mesoporous molecular sieve raw powder are mixed and ball-milled, and then calcined to obtain a dual-porous catalyst.

[0046] According to the present invention, in step (1), the metal oxide precursor aqueous solution comprises a metal salt and water; the metal salt is a water-soluble salt of an alkaline earth metal and / or a transition metal, preferably a nitrate of one or more of magnesium, calcium, strontium, barium and zinc.

[0047] According to the present invention, in step (1), the mass concentration of the metal oxide precursor aqueous solution is 0.2-3.0%, preferably 0.4-1.5%.

[0048] According to the present invention, in step (1), the weight ratio of the ZSM-11 molecular sieve to the metal oxide precursor aqueous solution is 1:(3-30), preferably 1:(8-20).

[0049] According to the present invention, in step (1), the contact reaction conditions include: temperature of 10-100° C., preferably 30-80° C.; time of 0.5-50 h, preferably 2-20 h. Preferably, in order to achieve a better mixing effect, the ZSM-11 molecular sieve and the metal oxide precursor aqueous solution can be mixed by rapid stirring or ultrasonic means to improve the mixing efficiency.

[0050] According to the present invention, in step (1), the dehydration method is not particularly limited and can be a dehydration method known in the art, such as: dehydration by evaporation using a rotary evaporator, or dehydration by heating and stirring.

[0051] According to the present invention, in step (1), the drying conditions include: temperature of 60-150° C., preferably 80-130° C.; time of 1-30 h, preferably 3-20 h.

[0052] According to the present invention, in step (2), the weight ratio of the microporous molecular sieve dry powder to the SBA-3 all-silica mesoporous molecular sieve raw powder is 1:(0.1-1.5), preferably 1:(0.3-0.8).

[0053] According to the present invention, in step (2), the ball milling is carried out in a ball mill, wherein the diameter of the grinding balls in the ball mill can be 2-3 mm; the number of grinding balls can be reasonably selected according to the size of the ball mill jar, and for a ball mill jar of 100-300 mL, 2-8 grinding balls can usually be used; the material of the grinding balls is agate or polytetrafluoroethylene, preferably agate. The conditions of the ball milling include: the rotation speed of the grinding balls can be 200-600 r / min, preferably 300-500 r / min; the temperature in the ball mill jar can be 30-90°C, preferably 40-80°C; the ball milling time can be 5-50h, preferably 8-24h.

[0054] According to the present invention, in step (2), the calcination conditions include: temperature of 450-650° C., preferably 500-600° C.; time of 5-40 h, preferably 8-20 h.

[0055] The third aspect of the present invention provides an application of the aforementioned dual-porous catalyst in the direct catalytic cracking of waste plastics to produce light olefins.

[0056] According to the present invention, the application comprises: under specific conditions, contacting waste plastic powder or particles with the dual-porous catalyst to react.

[0057] In the present invention, the conditions for contacting the waste plastic powder or particles with the birefringent catalyst include: the contact temperature can be 420-580°C, preferably 450-540°C; the contact pressure can be 0.01-1.0Mpa, preferably 0.05-0.5Mpa; the contact time can be 0.5-12h, preferably 1-5h; the weight ratio of the birefringent catalyst to the waste plastic powder or particles can be 1:(0.5-50), preferably 1:(2-30).

[0058] The present invention will be described in detail below through examples.

[0059] In the following examples and comparative examples:

[0060] The small-angle XRD test of the sample was carried out on a D8 ADVANCE high-power rotating target X-ray diffractometer produced by BRUKER AXS of Germany, with a scanning range of 0.5-10°.

[0061] The wide-angle XRD test of the sample was carried out on an X'Pert MPD X-ray powder diffractometer of Philips Company in the Netherlands, with a Cu Kα target and a scanning range of 2θ=5-90°.

[0062] The pore structure parameter analysis of the samples was carried out on an ASAP2020-M+C adsorption instrument purchased from Micromeritics, Inc., USA. The samples were vacuum degassed at 350°C for 4 hours before measurement, and the specific surface area of ​​the samples was calculated using the BET method, and the pore volume was calculated using the BJH model.

[0063] The elemental analysis experiment of the samples was carried out on an EagleⅢ energy dispersive X-ray fluorescence spectrometer produced by EDAX, USA.

[0064] The drying oven was produced by Shanghai Yiheng Scientific Instrument Co., Ltd., model DHG-9030A.

[0065] The muffle furnace is produced by CARBOLITE, model CWF1100.

[0066] Other reagents used in the examples and comparative examples were purchased from Sinopharm Chemical Reagent Co., Ltd. and were of analytical purity.

[0067] Example 1

[0068] This embodiment is intended to illustrate the bi-porous catalyst prepared by the present invention and its application in the reaction of producing light olefins from waste plastics.

[0069] (1) Preparation of SBA-3 all-silica mesoporous molecular sieve raw powder

[0070] The template agent hexadecyltrimethylammonium bromide was dissolved in deionized water, stirred at 25°C to dissolve it completely and turn it into a colorless transparent solution, sodium bromide was added first and stirred for 10 minutes to dissolve it, phosphoric acid was added and stirred for 10 minutes, and finally tetraethyl orthosilicate was slowly added to the above solution, and stirring was continued at 25°C for crystallization for 24 hours. The molar ratio of tetraethyl orthosilicate, hexadecyltrimethylammonium bromide, phosphoric acid, sodium bromide and water was 1:0.6:3:1.0:150. After the crystallization was completed, a white solid was obtained by centrifugal filtration. The white solid was washed with deionized water 5 times, and the solid product was dried at 90°C for 12 hours to obtain SBA-3 all-silica mesoporous molecular sieve raw powder A.

[0071] (2) Preparation of bi-porous catalysts

[0072] 9.6 g of magnesium nitrate hexahydrate was dissolved in 400 g of distilled water to prepare an aqueous solution. 36 g of ZSM-11 molecular sieve (SiO2 / Al2O3=80) was added to the above magnesium nitrate aqueous solution, stirred at 60°C for 5 h, and then the water was removed using a rotary evaporator. The solid product was dried at 110°C for 8 h to obtain microporous molecular sieve dry powder A.

[0073] The above-mentioned microporous molecular sieve dry powder A and 22g of SBA-3 all-silicon mesoporous molecular sieve raw powder A were added to a 300mL ball mill, and 6 agate grinding balls with a diameter of 2mm were placed to start ball milling. The temperature in the ball mill was controlled at 50°C, the speed of the grinding balls was 400r / min, and the ball milling time was 10h. The powder obtained after ball milling was calcined at 550°C for 16h to obtain a dual-porous catalyst A.

[0074] Based on the total weight of the catalyst A, the content of the ZSM-11 molecular sieve is 72% by weight, the content of the SBA-3 all-silicon mesoporous molecular sieve is 25% by weight, and the content of the magnesium oxide is 3% by weight.

[0075] The specific surface area of ​​catalyst A is 548 m 2 / g, pore volume 0.40cm 3 / g.

[0076] Figure 1 is the small-angle XRD spectrum of catalyst A, Figure 1The spectrum shows that the sample has three clearly visible diffraction peaks at small angles below 6°, proving that the mesoporous material in the catalyst has a typical two-dimensional hexagonal mesoporous structure. This shows that the SBA-3 all-silicon mesoporous molecular sieve still has a relatively regular mesoporous channel structure after being prepared into a catalyst, and the catalyst preparation process does not destroy the basic structure of the mesoporous molecular sieve.

[0077] Figure 2 is the wide-angle XRD spectrum of catalyst A, Figure 2 The spectrum shows that the wide-angle x-ray diffraction angles of the sample are mainly: 2θ = 7.9°, 8.8°, 23.1°, 24.0° and 45.2°. The above diffraction signals are consistent with the diffraction spectrum of ZSM-11 molecular sieve, indicating that the crystal phase of ZSM-11 molecular sieve has not changed significantly during the preparation of the catalyst and still maintains a good skeleton structure. In addition, there is no diffraction signal corresponding to the metal oxide in the wide-angle XRD spectrum, indicating that the metal oxide component is uniformly dispersed on the catalyst and the particle size is less than 2nm.

[0078] Figure 3 is the pore size distribution diagram of catalyst A, Figure 3 The spectrum shows that the sample has an obvious double-pore structure, with double pore diameters of 0.54nm and 2.5nm respectively. The pore with a diameter of 0.54nm is provided by ZSM-11 molecular sieve, and the pore with a diameter of 2.5nm is provided by SBA-3 all-silica mesoporous molecular sieve.

[0079] (3) Evaluation of the reaction performance of direct conversion of waste plastics to light olefins

[0080] The performance of the catalyst in the catalytic cracking reaction of waste plastics was evaluated in a fixed bed reactor. The catalyst loading was 10.0 g, the loading of waste polyethylene plastic particles was 50.0 g, the reaction temperature was 520°C, the reaction pressure was 0.1 MPa, the reaction time was 1 hour, and after the product was cooled and the gas and liquid were separated, the gas composition was analyzed by an Agilent 6890 gas chromatograph equipped with an Al2O3-S capillary column and a hydrogen flame detector (FID), and the quantitative analysis was performed using a programmed temperature rise and a correction factor; the liquid composition was analyzed by an Agilent 7890A gas chromatograph equipped with a PONA column. The reaction results are shown in Table 1.

[0081] Example 2

[0082] This embodiment is intended to illustrate the bi-porous catalyst prepared by the present invention and its application in the reaction of producing light olefins from waste plastics.

[0083] (1) Preparation of SBA-3 all-silica mesoporous molecular sieve

[0084] The template agent dodecyl trimethyl ammonium bromide was dissolved in deionized water, stirred at 20°C to dissolve it completely and turn it into a colorless transparent solution, sodium nitrate was added first and stirred for 20 minutes to dissolve it, then acetic acid was added and stirred for 10 minutes, and finally tetraethyl orthosilicate was slowly added to the above solution, and stirred and crystallized for 50 hours at 20°C. The molar ratio of tetraethyl orthosilicate, dodecyl trimethyl ammonium bromide, acetic acid, sodium nitrate and water was 1:1.2:6:2.0:200. After the crystallization was completed, a white solid was obtained by centrifugal filtration. The white solid was washed 8 times with deionized water, and the solid product was dried at 110°C for 6 hours to obtain SBA-3 all-silica mesoporous molecular sieve raw powder B.

[0085] (2) Preparation of bi-porous catalysts

[0086] 2.1 g of strontium nitrate was dissolved in 500 g of distilled water to prepare an aqueous solution. 39 g of ZSM-11 molecular sieve (SiO2 / Al2O3=90) was added to the above strontium nitrate aqueous solution, stirred at 80°C for 2 h, and then the water was removed using a rotary evaporator. The solid product was dried at 130°C for 3 h to obtain microporous molecular sieve dry powder B.

[0087] The above-mentioned microporous molecular sieve dry powder B and 16g of SBA-3 all-silicon mesoporous molecular sieve raw powder B were added to a 300mL ball mill, and 8 agate grinding balls with a diameter of 2mm were placed to start ball milling. The temperature in the ball mill was controlled at 80°C, the speed of the grinding balls was 500r / min, and the ball milling time was 8h. The powder obtained after ball milling was calcined at 600°C for 8h to obtain a dual-porous catalyst B.

[0088] Based on the total weight of the catalyst B, the content of the ZSM-11 molecular sieve is 78% by weight, the content of the SBA-3 all-silicon mesoporous molecular sieve is 20% by weight, and the content of the strontium oxide is 2% by weight.

[0089] The specific surface area of ​​catalyst B is 535m 2 / g, pore volume 0.38cm 3 / g, and the double pore diameters are 0.53nm and 2.8nm respectively.

[0090] The reaction performance of Catalyst B was tested according to the reaction performance evaluation method for direct conversion of waste plastics to light olefins in step (3) of Example 1. The evaluation results are listed in Table 1.

[0091] Example 3

[0092] This embodiment is intended to illustrate the bi-porous catalyst prepared by the present invention and its application in the reaction of producing light olefins from waste plastics.

[0093] (1) Preparation of SBA-3 all-silica mesoporous molecular sieve

[0094] The template agent octadecyl trimethyl ammonium bromide was dissolved in deionized water, stirred at 40°C to dissolve it completely and turn it into a colorless transparent solution, potassium chloride was added first and stirred for 10 minutes to dissolve it, then phosphoric acid was added and stirred for 10 minutes, and finally water glass was slowly added to the above solution, and stirred and crystallized at 40°C for 8 hours. The molar ratio of water glass, octadecyl trimethyl ammonium bromide, phosphoric acid, potassium chloride and water is 1:0.1:1:0.5:50. After the crystallization is completed, centrifugal filtration is performed to obtain a white solid. The white solid was washed with deionized water 3 times, and the solid product was dried at 70°C for 20 hours to obtain SBA-3 all-silica mesoporous molecular sieve raw powder C.

[0095] (2) Preparation of bi-porous catalysts

[0096] 5.8 g of calcium nitrate was dissolved in 300 g of distilled water to prepare an aqueous solution. 33 g of ZSM-11 molecular sieve (SiO2 / Al2O3=50) was added to the above calcium nitrate aqueous solution, stirred at 30°C for 20 h, and then the water was removed using a rotary evaporator. The solid product was dried at 80°C for 20 h to obtain microporous molecular sieve dry powder C.

[0097] The above-mentioned microporous molecular sieve dry powder C and 28g of SBA-3 all-silicon mesoporous molecular sieve raw powder C were added to a 300mL ball mill, and 4 agate grinding balls with a diameter of 2mm were placed to start ball milling. The temperature in the ball mill was controlled at 40°C, the speed of the grinding balls was 300r / min, and the ball milling time was 24h. The powder obtained after ball milling was calcined at 500°C for 20h to obtain a dual-porous catalyst C.

[0098] Based on the total weight of the catalyst C, the content of the ZSM-11 molecular sieve is 66% by weight, the content of the SBA-3 all-silicon mesoporous molecular sieve is 30% by weight, and the content of the calcium oxide is 4% by weight.

[0099] The specific surface area of ​​catalyst C is 570 m 2 / g, pore volume 0.43cm 3 / g, and the double pore diameters are 0.54nm and 2.4nm respectively.

[0100] The reaction performance of Catalyst C was tested according to the reaction performance evaluation method for direct conversion of waste plastics to light olefins in step (3) of Example 1. The evaluation results are listed in Table 1.

[0101] Example 4

[0102] This embodiment is intended to illustrate the bi-porous catalyst prepared by the present invention and its application in the reaction of producing light olefins from waste plastics.

[0103] SBA-3 all-silica mesoporous molecular sieve raw powder A was prepared in the same manner as step (1) in Example 1.

[0104] (2) Preparation of bi-porous catalysts

[0105] 1.8 g of zinc nitrate hexahydrate was dissolved in 400 g of distilled water to prepare an aqueous solution. 42 g of ZSM-11 molecular sieve (SiO2 / Al2O3=90) was added to the above zinc nitrate aqueous solution, stirred at 60°C for 5 h, and then the water was removed using a rotary evaporator. The solid product was dried at 110°C for 8 h to obtain microporous molecular sieve dry powder D.

[0106] The above-mentioned microporous molecular sieve dry powder D and 12g of SBA-3 all-silicon mesoporous molecular sieve raw powder A were added to a 300mL ball mill, and 6 agate grinding balls with a diameter of 2mm were placed to start ball milling. The temperature in the ball mill was controlled at 50°C, the speed of the grinding balls was 400r / min, and the ball milling time was 10h. The powder obtained after ball milling was calcined at 550°C for 16h to obtain a dual-porous catalyst D.

[0107] Based on the total weight of the catalyst D, the content of the ZSM-11 molecular sieve was 84% ​​by weight, the content of the SBA-3 all-silicon mesoporous molecular sieve was 15% by weight, and the content of the zinc oxide was 1% by weight.

[0108] The specific surface area of ​​catalyst D is 500m 2 / g, pore volume 0.34cm 3 / g, and the double pore diameters are 0.53nm and 2.5nm respectively.

[0109] The reaction performance of Catalyst D was tested using the same reaction performance evaluation method for direct conversion of waste plastics to light olefins as in step (3) of Example 1. The evaluation results are listed in Table 1.

[0110] Example 5

[0111] This embodiment is intended to illustrate the bi-porous catalyst prepared by the present invention and its application in the reaction of producing light olefins from waste plastics.

[0112] SBA-3 all-silica mesoporous molecular sieve raw powder B was prepared in the same manner as step (1) in Example 2.

[0113] (2) Preparation of bi-porous catalysts

[0114] 4.3 g of barium nitrate was dissolved in 300 g of distilled water to prepare an aqueous solution. 30 g of ZSM-11 molecular sieve (SiO2 / Al2O3=35) was added to the above barium nitrate aqueous solution, stirred at 80°C for 2 h, and then the water was removed using a rotary evaporator. The solid product was dried at 130°C for 3 h to obtain microporous molecular sieve dry powder E.

[0115] The above-mentioned microporous molecular sieve dry powder E and 27g of SBA-3 all-silicon mesoporous molecular sieve raw powder B were added to a 300mL ball mill, and 8 agate grinding balls with a diameter of 2mm were placed to start ball milling. The temperature in the ball mill was controlled at 80°C, the speed of the grinding balls was 500r / min, and the ball milling time was 8h. The powder obtained after ball milling was calcined at 600°C for 8h to obtain a dual-porous catalyst E.

[0116] Based on the total weight of the catalyst E, the content of the ZSM-11 molecular sieve is 60% by weight, the content of the SBA-3 all-silicon mesoporous molecular sieve is 35% by weight, and the content of the barium oxide is 5% by weight.

[0117] The specific surface area of ​​catalyst E is 590 m 2 / g, pore volume 0.46cm 3 / g, and the double pore diameters are 0.55nm and 2.8nm respectively.

[0118] The reaction performance of Catalyst E was tested using the same reaction performance evaluation method for direct conversion of waste plastics to light olefins as in step (3) of Example 1. The evaluation results are listed in Table 1.

[0119] Example 6

[0120] This embodiment is intended to illustrate the bi-porous catalyst prepared by the present invention and its application in the reaction of producing light olefins from waste plastics.

[0121] SBA-3 all-silica mesoporous molecular sieve raw powder A was prepared in the same manner as step (1) in Example 1.

[0122] (2) Preparation of bi-porous catalysts

[0123] 45g ZSM-11 molecular sieve (SiO2 / Al2O3=280) and 8g SBA-3 all-silicon mesoporous molecular sieve raw powder A were added to a 300mL ball mill, and 6 agate grinding balls with a diameter of 2mm were placed to start ball milling. The temperature in the ball mill was controlled at 50°C, the speed of the grinding balls was 400r / min, and the ball milling time was 10h. The powder obtained after ball milling was calcined at 550°C for 16h to obtain a dual-porous catalyst F.

[0124] Based on the total weight of the catalyst F, the content of the ZSM-11 molecular sieve is 90% by weight, and the content of the SBA-3 all-silicon mesoporous molecular sieve is 10% by weight.

[0125] The specific surface area of ​​catalyst F is 420 m 2 / g, pore volume 0.30cm 3 / g, and the double pore diameters are 0.54nm and 2.5nm respectively.

[0126] The reaction performance of Catalyst F was tested using the same reaction performance evaluation method for direct conversion of waste plastics to light olefins as in step (3) of Example 1. The evaluation results are listed in Table 1.

[0127] Example 7

[0128] This embodiment is intended to illustrate the bi-porous catalyst prepared by the present invention and its application in the reaction of producing light olefins from waste plastics.

[0129] SBA-3 all-silica mesoporous molecular sieve raw powder B was prepared in the same manner as step (1) in Example 2.

[0130] (2) Preparation of bi-porous catalysts

[0131] 19.2 g of magnesium nitrate hexahydrate was dissolved in 600 g of distilled water to prepare an aqueous solution. 27 g of ZSM-11 molecular sieve (SiO2 / Al2O3=35) was added to the above magnesium nitrate aqueous solution, stirred at 80°C for 2 h, and then the water was removed using a rotary evaporator. The solid product was dried at 130°C for 3 h to obtain microporous molecular sieve dry powder G.

[0132] The above-mentioned microporous molecular sieve dry powder G and 30g of SBA-3 all-silicon mesoporous molecular sieve raw powder B were added to a 300mL ball mill, and 8 agate grinding balls with a diameter of 2mm were placed to start ball milling. The temperature in the ball mill was controlled at 80℃, the speed of the grinding balls was 500r / min, and the ball milling time was 8h. The powder obtained after ball milling was calcined at 600℃ for 8h to obtain a dual-porous catalyst G.

[0133] Based on the total weight of the catalyst G, the content of the ZSM-11 molecular sieve was 54% by weight, the content of the SBA-3 all-silicon mesoporous molecular sieve was 40% by weight, and the content of the magnesium oxide was 6% by weight.

[0134] The specific surface area of ​​catalyst G is 630 m 2 / g, pore volume 0.50cm 3 / g, and the double pore diameters are 0.55nm and 2.8nm respectively.

[0135] The reaction performance of Catalyst G was tested using the same reaction performance evaluation method for direct conversion of waste plastics to light olefins as in step (3) of Example 1. The evaluation results are listed in Table 1.

[0136] Comparative Example 1

[0137] SBA-3 all-silica mesoporous molecular sieve raw powder A was prepared in the same manner as step (1) in Example 1.

[0138] (2) Preparation of bi-porous catalysts

[0139] 10.2 g of barium nitrate was dissolved in 200 g of distilled water to prepare an aqueous solution. 15 g of ZSM-11 molecular sieve (SiO2 / Al2O3=80) was added to the above barium nitrate aqueous solution, stirred at 60°C for 5 h, and then the water was removed using a rotary evaporator. The solid product was dried at 110°C for 8 h to obtain microporous molecular sieve dry powder D1.

[0140] The above-mentioned microporous molecular sieve dry powder D1 and 46g of SBA-3 all-silicon mesoporous molecular sieve raw powder A were added to a 300mL ball mill, and 6 agate grinding balls with a diameter of 2mm were placed to start ball milling. The temperature in the ball mill was controlled at 50°C, the speed of the grinding balls was 400r / min, and the ball milling time was 10h. The powder obtained after ball milling was calcined at 550°C for 16h to obtain the dual-porous catalyst D1.

[0141] Based on the total weight of the catalyst D1, the content of the ZSM-11 molecular sieve was 30% by weight, the content of the SBA-3 all-silicon mesoporous molecular sieve was 58% by weight, and the content of the barium oxide was 12% by weight.

[0142] The specific surface area of ​​catalyst D1 is 800m 2 / g, pore volume 0.60cm 3 / g, and the double pore diameters are 0.54nm and 2.5nm respectively.

[0143] The reaction performance of catalyst D1 was tested using the same reaction performance evaluation method for direct conversion of waste plastics to light olefins as in step (3) of Example 1. The evaluation results are listed in Table 1.

[0144] Comparative Example 2

[0145] SBA-3 all-silica mesoporous molecular sieve raw powder B was prepared in the same manner as step (1) in Example 2.

[0146] (2) Preparation of bi-porous catalysts

[0147] 47.5g ZSM-11 molecular sieve (SiO2 / Al2O3=35) and 4g SBA-3 all-silicon mesoporous molecular sieve raw powder B were added to a 300mL ball mill, and 8 agate grinding balls with a diameter of 2mm were placed to start ball milling. The temperature in the ball mill was controlled at 80°C, the speed of the grinding balls was 500r / min, and the ball milling time was 8h. The powder obtained after ball milling was calcined at 600°C for 8h to obtain a dual-porous catalyst D2.

[0148] Based on the total weight of the catalyst D2, the content of the ZSM-11 molecular sieve is 95% by weight, and the content of the SBA-3 all-silicon mesoporous molecular sieve is 5% by weight.

[0149] The specific surface area of ​​catalyst D2 is 380m 2 / g, pore volume 0.27cm 3 / g, and the double pore diameters are 0.55nm and 2.8nm respectively.

[0150] The reaction performance of catalyst D2 was tested using the same reaction performance evaluation method for direct conversion of waste plastics to light olefins as in step (3) of Example 1. The evaluation results are listed in Table 1.

[0151] Comparative Example 3

[0152] SBA-3 all-silicon mesoporous molecular sieve raw powder A was prepared in the same manner as step (1) in Example 1, and SBA-3 all-silicon mesoporous molecular sieve raw powder A was calcined at 550° C. for 16 h to obtain SBA-3 all-silicon mesoporous molecular sieve A.

[0153] The specific surface area of ​​SBA-3 all-silica mesoporous molecular sieve A is 1217m 2 / g, pore volume 0.92cm 3 / g, pore size is 2.5nm.

[0154] Eliminate step (2) in Example 1.

[0155] The reaction performance of SBA-3 all-silica mesoporous molecular sieve A was tested using the same reaction performance evaluation method for direct conversion of waste plastics to light olefins as in step (3) of Example 1. The evaluation results are listed in Table 1.

[0156] Comparative Example 4

[0157] The catalyst was prepared in the same manner as in Example 1, except that:

[0158] Cancel step (1) in Example 1.

[0159] Catalyst D3 was prepared according to the following steps: 9.6 g of magnesium nitrate hexahydrate was dissolved in 400 g of distilled water to prepare an aqueous solution. 36 g of ZSM-11 molecular sieve (SiO2 / Al2O3=80) was added to the above magnesium nitrate aqueous solution, stirred at 60°C for 5 h, and then the water was removed by a rotary evaporator. The solid product was dried at 110°C for 8 h and calcined at 550°C for 16 h to obtain catalyst D3.

[0160] The reaction performance of catalyst D3 was tested using the same reaction performance evaluation method for direct conversion of waste plastics to light olefins as in step (3) of Example 1. The evaluation results are listed in Table 1.

[0161] Comparative Example 5

[0162] The catalyst was prepared in the same manner as in Example 1, except that:

[0163] Eliminate step (1) and step (2) in Example 1.

[0164] The reaction performance of ZSM-11 molecular sieve (SiO2 / Al2O3=80) was tested according to the same reaction performance evaluation method for direct conversion of waste plastics to light olefins as in step (3) of Example 1. The evaluation results are listed in Table 1.

[0165] Comparative Example 6

[0166] SBA-3 all-silica mesoporous molecular sieve raw powder A was prepared in the same manner as step (1) in Example 1.

[0167] The ball milling process in step (2) of Example 1 is eliminated.

[0168] (2) Preparation of bi-porous catalysts

[0169] 10.2 g of barium nitrate was dissolved in 200 g of distilled water to prepare an aqueous solution. 15 g of ZSM-11 molecular sieve (SiO2 / Al2O3=80) was added to the above barium nitrate aqueous solution, stirred at 60°C for 5 h, and then the water was removed using a rotary evaporator. The solid product was dried at 110°C for 8 h to obtain microporous molecular sieve dry powder D1.

[0170] The above-mentioned microporous molecular sieve dry powder D1 and 46 g of SBA-3 all-silica mesoporous molecular sieve raw powder A were mixed and calcined at 550° C. for 16 h to obtain a dual-porous catalyst D4.

[0171] The reaction performance of catalyst D4 was tested by the same reaction performance evaluation method for direct conversion of waste plastics to light olefins as in step (3) of Example 1. The evaluation results are listed in Table 1.

[0172] Comparative Example 7

[0173] The catalyst was prepared in the same manner as in Example 1, except that:

[0174] Cancel step (1) in Example 1.

[0175] Catalyst D5 was prepared in the same manner as step (2) in the example, except that the SBA-3 all-silicon mesoporous molecular sieve powder A was replaced with commercially available silicon dioxide powder (specific surface area of ​​274 m 2 / g, pore volume 0.54cm 3 / g), the specific process is as follows:

[0176] 9.6 g of magnesium nitrate hexahydrate was dissolved in 400 g of distilled water to prepare an aqueous solution. 36 g of ZSM-11 molecular sieve (SiO2 / Al2O3=80) was added to the above magnesium nitrate aqueous solution, stirred at 60°C for 5 h, and then the water was removed using a rotary evaporator. The solid product was dried at 110°C for 8 h to obtain microporous molecular sieve dry powder A.

[0177] The above-mentioned microporous molecular sieve dry powder A and 12.5g of commercially available silicon dioxide powder (specific surface area 274m 2 / g, pore volume 0.54cm 3 / g) was added into a 300mL ball mill, and 6 agate grinding balls with a diameter of 2mm were placed to start ball milling. The temperature in the ball mill was controlled at 50°C, the speed of the grinding balls was 400r / min, and the ball milling time was 10h. The powder obtained after ball milling was calcined at 550°C for 16h to obtain a bi-porous catalyst D5.

[0178] The reaction performance of catalyst D5 was tested using the same reaction performance evaluation method for direct conversion of waste plastics to light olefins as in step (3) of Example 1. The evaluation results are listed in Table 1.

[0179] Table 1

[0180]

[0181] It can be seen from the above results that the dual-hole catalyst provided by the present invention can directly catalyze the conversion of waste plastics into light olefins. The conversion rate of waste plastics is 100%, and the yield of light olefins is high.

[0182] In Comparative Example 1, the content of SBA-3 all-silicon mesoporous molecular sieve is too high, the content of ZSM-11 molecular sieve is too low, and the content of metal oxide is not within the range defined by the present invention. Due to the small number of acidic centers on the catalyst and insufficient activation sites during the reaction, the raw material conversion rate and the yield of light olefins are low.

[0183] In Comparative Example 2, the content of SBA-3 all-silicon mesoporous molecular sieve is too low, and the content of ZSM-11 molecular sieve is too high. Due to the small number of macropores in the catalyst, the diffusion of reactants and product molecules is hindered during the reaction, resulting in a low yield of light olefins.

[0184] In Comparative Example 3, only SBA-3 all-silicon mesoporous molecular sieve is used as a catalyst. Since the surface acidity of the all-silicon mesoporous molecular sieve is extremely weak, it is not conducive to the high molecular weight cracking reaction of waste plastics, resulting in a low conversion rate and a low yield of light olefins.

[0185] In Comparative Example 4, the catalyst contains only ZSM-11 molecular sieve and metal oxide, and no SBA-3 all-silicon mesoporous molecular sieve is added. Since the catalyst contains almost no mesoporous channels, the diffusion of reactant and product molecules during the reaction is severely hindered, resulting in a low yield of light olefins.

[0186] In Comparative Example 5, the catalyst contains only ZSM-11 molecular sieve, and does not contain SBA-3 all-silicon mesoporous molecular sieve and metal oxide. Since the catalyst contains almost no mesoporous channels, the diffusion of reactant and product molecules during the reaction is severely hindered, resulting in a low yield of light olefins.

[0187] In Comparative Example 6, the ball milling process was omitted, and the ZSM-11 molecular sieve and the SBA-3 all-silicon mesoporous molecular sieve were directly mixed. Since the ZSM-11 molecular sieve with an acidic center and the SBA-3 molecular sieve with a mesoporous structure were not mixed uniformly, the yield of light olefins was low.

[0188] In Comparative Example 7, commercially available silica powder was used to replace the SBA-3 all-silicon mesoporous molecular sieve. Since the mesoporous channel structure of the commercially available silica was irregular, the yield of light olefins was low.

[0189] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A dual-pore catalyst, characterized in that: The dual-porous catalyst comprises ZSM-11 molecular sieve, SBA-3 all-silicon mesoporous molecular sieve and optional metal oxide, and based on the total weight of the dual-porous catalyst, the content of the ZSM-11 molecular sieve is 54-90% by weight, the content of the SBA-3 all-silicon mesoporous molecular sieve is 10-40% by weight, and the content of the metal oxide is 0-6% by weight; The specific surface area of ​​the dual-pore catalyst is 420-630 m 2 / g, and the pore volume is 0.3-0.5mL / g.

2. The dual-pore catalyst according to claim 1, wherein Based on the total weight of the dual-pore catalyst, the content of the ZSM-11 molecular sieve is 60-84% by weight, the content of the SBA-3 all-silicon mesoporous molecular sieve is 15-35% by weight, and the content of the metal oxide is 1-5% by weight; Preferably, based on the total weight of the dual-pore catalyst, the content of the ZSM-11 molecular sieve is 66-78% by weight, the content of the SBA-3 all-silicon mesoporous molecular sieve is 20-30% by weight, and the content of the metal oxide is 2-4% by weight.

3. The dual-pore catalyst according to claim 1 or 2, wherein: The specific surface area of ​​the dual-pore catalyst is 500-590m 2 / g, and the pore volume is 0.34-0.46mL / g; preferably, the specific surface area of ​​the dual-pore catalyst is 535-570m 2 / g, pore volume is 0.38-0.43mL / g; And / or, the pore size of the dual-pore catalyst is bimodal, with the micropore size being 0.4-0.6 nm and the mesopore size being 2-4 nm.

4. The dual-pore catalyst according to claim 1 or 2, wherein: The SiO2 / Al2O3 molar ratio of the ZSM-11 molecular sieve is 30-300.

5. The dual-pore catalyst according to claim 1 or 2, wherein: The metal oxide is an alkaline earth metal oxide and / or a transition metal oxide; Preferably, the metal oxide is selected from one or more of magnesium oxide, calcium oxide, strontium oxide, barium oxide and zinc oxide.

6. The dual-pore catalyst according to claim 1 or 2, wherein: The preparation method of the SBA-3 all-silicon mesoporous molecular sieve raw powder comprises: mixing a template, a silicon source, an inorganic acid, a metal salt and water to obtain a mixture, and crystallizing, filtering, washing and drying the mixture to obtain the SBA-3 all-silicon mesoporous molecular sieve raw powder.

7. The dual-pore catalyst according to claim 6, wherein The template agent is a cationic surfactant, preferably one or more of dodecyltrimethylammonium bromide, tetradecyltrimethylammonium bromide, hexadecyltrimethylammonium bromide and octadecyltrimethylammonium bromide; And / or, the silicon source is an organic silicon source and / or an inorganic silicon source, preferably tetraethyl orthosilicate and / or water glass; and / or, the inorganic acid is selected from one or more of hydrochloric acid, sulfuric acid, nitric acid, phosphoric acid, acetic acid and citric acid, preferably phosphoric acid and / or acetic acid; and / or, the metal salt is selected from one or more of chlorides, bromides, nitrates and sulfates of alkali metals, preferably one or more of sodium nitrate, sodium chloride, sodium bromide, sodium sulfate, potassium nitrate, potassium chloride, potassium bromide and potassium sulfate; And / or, the molar ratio of the silicon source, template, inorganic acid, metal salt and water is 1: (0.05-2.0): (0.5-10): (0.2-5.0): (20-400); preferably 1: (0.1-1.2): (1-6): (0.5-2.0): (50-200).

8. A method for preparing a dual-porous catalyst according to any one of claims 1 to 7, characterized in that: The preparation method comprises: (1) mixing and contacting a ZSM-11 molecular sieve and an optional aqueous solution of a metal oxide precursor to react; then removing water and drying to obtain a microporous molecular sieve dry powder; (2) The microporous molecular sieve dry powder and the SBA-3 all-silica mesoporous molecular sieve raw powder are mixed and ball-milled, and then calcined to obtain a dual-porous catalyst.

9. The preparation method according to claim 8, wherein: The metal oxide precursor aqueous solution comprises a metal salt and water; the metal salt is a water-soluble salt of an alkaline earth metal and / or a transition metal, preferably a nitrate of one or more of magnesium, calcium, strontium, barium and zinc; And / or, the mass concentration of the metal oxide precursor aqueous solution is 0.2-3.0%; and / or, the weight ratio of the ZSM-11 molecular sieve to the metal oxide precursor aqueous solution is 1:(3-30); And / or, the weight ratio of the microporous molecular sieve dry powder to the SBA-3 all-silica mesoporous molecular sieve raw powder is 1:(0.1-1.5), preferably 1:(0.3-0.8).

10. The preparation method according to claim 8, wherein: The contact reaction conditions include: temperature of 10-100°C and time of 0.5-50h; And / or, the ball milling conditions include: the rotation speed of the grinding balls is 200-600 r / min, the temperature in the ball mill is 30-90° C., and the ball milling time is 5-50 h; And / or, the calcination conditions include: temperature of 450-650° C. and time of 5-40 h.

11. Use of the bi-porous catalyst according to any one of claims 1 to 7 in the direct catalytic cracking of waste plastics to produce light olefins.

12. The use according to claim 11, wherein: The application comprises: contacting waste plastic powder or particles with the dual-porous catalyst to react; And / or, the contact conditions include: temperature of 420-580°C, pressure of 0.01-1MPa, and contact time of 0.5-12h; And / or, the weight ratio of the bi-porous catalyst to the waste plastic powder or particles is 1:(0.5-50).

Citation Information

Patent Citations

  • Light gasoline cracking catalyst and preparation method thereof, and catalytic cracking method

    CN111167504A

  • C4 olefin cracking catalyst and preparation method thereof, and catalytic cracking method

    CN111167509A

  • Catalyst for preparing low-carbon olefin through catalytic cracking of waste plastics and preparation method of catalyst

    CN113398982A

  • Efficient and selective conversion of high-density polyethylene into valuable hydrocarbons

    US20230211326A1